2018
DOI: 10.1097/gox.0000000000001738
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Gender-affirming Surgery in Insured Patients in the United States

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
107
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 158 publications
(127 citation statements)
references
References 8 publications
2
107
0
Order By: Relevance
“…Gender-affirming surgery is currently recommended for individuals aged at least 16 years of age but often ≥18 years 12. Recent insurance database analysis and patient-reported outcome studies identified patients as young as 14 years old undergoing a gender-affirming mastectomy 18 19. Some research works suggest there are psychosocial benefits to individuals receiving gender mastectomy in their teens 18 20–22.…”
Section: Medical Gender Affirmation: Risks and Benefits In Minorsmentioning
confidence: 99%
“…Gender-affirming surgery is currently recommended for individuals aged at least 16 years of age but often ≥18 years 12. Recent insurance database analysis and patient-reported outcome studies identified patients as young as 14 years old undergoing a gender-affirming mastectomy 18 19. Some research works suggest there are psychosocial benefits to individuals receiving gender mastectomy in their teens 18 20–22.…”
Section: Medical Gender Affirmation: Risks and Benefits In Minorsmentioning
confidence: 99%
“…DISCUSSION An estimated 0.6% of the US population identifies as transgender and an increasing number of these individuals seek gender-affirming surgery. 7 As a result, pathologists will be more frequently encountering specimens from genderaffirming surgery. Currently, there is a lack of established guidelines on how to best sample breast tissue from these surgeries.…”
Section: Comparative Analysis Between Gender-affirming Surgery and Rmmentioning
confidence: 99%
“…Despite this phalloplasty chaos, we emphasize that masculinizing genital GCS is medically necessary with well-demonstrated health benefits for properly selected patients. With an increased volume of these procedures being performed [78] , and with further research in all domains, we anticipate continual advances in this difficult and challenging area of surgery.…”
Section: Stagingmentioning
confidence: 99%